A Text Categorization Model Based on Hidden Markov Models - Yi, Kwan; Beheshti, Jamshid (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
The Hidden Markov model (HMM) has been successfully used for speech recognition, part of speech tagging, and pattern recognition. In this study, we apply the HMM to automatically categorize digital documents into a standard library classification scheme. In the proposed framework, A HMM-based system is viewed as a model to generate a list of words and each document is seen as. . .